2019
DOI: 10.1002/est2.73
|View full text |Cite
|
Sign up to set email alerts
|

Few‐layer graphene coated on indium tin oxide electrodes prepared by chemical vapor deposition and their enhanced glucose electrooxidation activity

Abstract: At present, few‐layer graphene is deposited on copper (Cu) foil by chemical vapor deposition (CVD) method. Then, the few‐layer graphenes produced on the Cu foil are coated onto the indium tin oxide (ITO) electrode to investigate their glucose electrooxidation activities. Hexane and hydrogen flow rate and deposition time parameters with CVD method are examined on different Cu foils. These electrodes are characterized by scanning electron microscopy‐energy dispersive X‐ray analysis (SEM‐EDX), X‐ray photoelectron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In order to increase the activity and energy density in glucose electrooxidation, it is important to develop catalysts made to have a high catalytic effect. In the literature, few‐layer graphene/ITO, 41 N‐doped few‐layer graphene/ITO, 42 Pt‐graphene/ITO, 37 Pd‐N doped‐G/ITO, 43 and also the catalysts given in Table 1 were studied to increase glucose electrooxidation. Ozok et al 12 specified that the benzothiophene organic catalyst indicated catalytic activity for glucose electrooxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the activity and energy density in glucose electrooxidation, it is important to develop catalysts made to have a high catalytic effect. In the literature, few‐layer graphene/ITO, 41 N‐doped few‐layer graphene/ITO, 42 Pt‐graphene/ITO, 37 Pd‐N doped‐G/ITO, 43 and also the catalysts given in Table 1 were studied to increase glucose electrooxidation. Ozok et al 12 specified that the benzothiophene organic catalyst indicated catalytic activity for glucose electrooxidation reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Glucose oxidation has been realized as an electrochemical sensor for the control and rapid diagnosis of initial diabetes. [15][16][17][18][19] Researchers have shown that when glucose is fed into direct fuel cells, it produces 24 electrons. However, it is difficult to break and oxidize since glucose has a very stable molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose is an abundant monosaccharide in nature. Glucose oxidation has been realized as an electrochemical sensor for the control and rapid diagnosis of initial diabetes [15–19] . Researchers have shown that when glucose is fed into direct fuel cells, it produces 24 electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Glucose electrooxidation (GAEO) to gluconic acid reactions are given as follows [23,24] (3) The development of anode catalysts with high GAEO activity is crucial for the commercialization of the direct glucose fuel cell. Hence, the anode catalyst performance of Fe 15 Pt 85 [25], Ni-Fe [26], Ni-Co [27], Au [28], Pt [29], G-ITO [30], AgNi [31], Pd [32], FeCo 2 O 4 [33], and Pd-Au [34] nanocatalysts have been investigated for direct GA fuel cells (DGFC). For instance, Chai et al reported that Pd 3 Cu-B/C nanocatalyst synthesized by a simple aqueous phase approach method had high GAEO activity and stability for GAEO reaction in fuel cell [35].…”
Section: Introductionmentioning
confidence: 99%